Determining the Readiness of Future Physical Education Teachers to Implement Adaptive Physical Education in Schools for Students with Hearing Impairments - Nosko, Mykola; Troyanovskaya, Maria (Physical Education Theory and Methodology, 2026)
Background. This article presents the results of a comprehensive study on how prepared future physical education teachers are to implement adaptive physical education for children with hearing impairments. The study’s relevance stems from Ukraine’s growing need for inclusive education, and the necessity to ensure that children with sensory disabilities have access to physical activity. Inclusive education means creating equal learning opportunities for all students, including those with hearing impairments. In this context, physical education supports both health and socialization. Objectives. The study aimed to provide a theoretical justification, conduct an empirical investigation, assess the readiness of future physical education teachers to implement adaptive physical education in educational institutions that enroll students with hearing impairments, and develop practical recommendations to improve teachers’ professional training. The article examines the structure of professional readiness of future physical education teachers. It presents the findings of an empirical study on readiness levels and analyzes the factors that influence their development. Materials and Methods. The study involved 186 students of T.H. Shevchenko National University “Chernihiv Collegium.” The research examined the participants’ knowledge of adaptive physical education, their skills in working with students with hearing impairments, and their motivational value and attitudes toward inclusive education. The objective of the study was to assess the level of professional readiness of students majoring in Physical Education to implement adaptive physical education in schools with inclusive forms of education for children with hearing impairments. Readiness was evaluated based on four key components: cognitive, motivational–value, operational–practical, and communicative–reflective. Results. The findings indicate insufficient practical training and limited proficiency in sign language, although the majority of students demonstrated positive motivation toward inclusion. A training model that includes a theoretical course, practical modules, volunteer activities, internships, and support from an experienced mentor is proposed. Promising directions for improving educational programs were identified. Conclusions. The readiness of future teachers to implement adaptive physical education in schools educating children with hearing impairments is a key factor in the successful implementation of inclusive education. The study contributes to the development of adaptive physical education and to the training of teaching professionals for work in inclusive educational environments.